Post-Operative Recovery of Lumbar Disc Herniation - Florentina Nechita (Editura Universitatii Transilvania din Brasov, 2023)
Lumbar disc herniation is a common problem among people, especially those who are professionally active. The research emphasizes how to relieve lumbar pain, pain is the central symptom of disc herniation, and this can be solved by toning the hypotonic muscles. This will contribute to improving the functionality of the spine and even overcoming the patient's fear of movement after the operation. Thus, kinetic treatment methods and means will be applied to facilitate movements, reduce pain, and reintegrate the patient into professional activity.